Welcome to the Outback: The Paradoxes of Living and Teaching in Remote Western Australian Schools - Lock, Graeme; Budgen, Fiona; Lunay, Ralph; Oakley, Grace (Australian and International Journal of Rural Education, 2012)
Teaching in remote schools can prove to be a challenging experience. Twenty three teachers from remote schools, located in Western Australia, were interviewed about their teaching and living experiences in isolated communities. The interview questions were designed to elicit information regarding three areas: demographic information; reasons for applying for a position in an isolated school and living in a remote community; and, professional factors impacting on the respondents. Interviews were conducted during a residential professional development session and involved twenty-three teachers with wide ranging ages and teaching experience. These teachers identified a number of affective factors including what attracted them to teach in remote communities, what they liked and disliked about their lifestyle and why they decided to stay in the community in which they lived and taught. Professional factors identified included teaching and learning issues; curriculum and assessment; catering for individual needs; liaising with Aboriginal Education Workers; engaging and managing students; pedagogical issues and professional development. Teachers also identified the professional benefits and challenges of teaching in remote communities. The article concludes with a short discussion on the paradoxes of living and teaching in isolated locations, followed by outlining three recommendations derived from the interview data.